2022
DOI: 10.1097/sla.0000000000005759
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort of Alcohol Use and Alcohol-related Problems Before and After Metabolic and Bariatric Surgery in Adolescents

Abstract: Objective: To describe alcohol use, alcohol-related harm, and alcohol-related problems preoperatively and up to 8 years following metabolic and bariatric surgery (MBS) in adolescents. Background: Risk for alcohol use and alcohol use disorders (AUD) increases post-Roux-en-Y gastric bypass and vertical sleeve gastrectomy in adults. However, data are lacking in adolescents who undergo MBS. Methods: This study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Estimates suggest that between 2%-33% of adult bariatric surgery patients develop AUD, with the peak incidence occurring in the second post-operative year[ 3 , 4 , 7 , 8 ]. This risk may be higher in adolescent bariatric surgery recipients with a recent multi-center study reporting an AUD prevalence of approximately 45% eight years post-surgery[ 9 ].…”
Section: Epidemiology Of Alcohol Use After Bariatric Surgerymentioning
confidence: 99%
“…Estimates suggest that between 2%-33% of adult bariatric surgery patients develop AUD, with the peak incidence occurring in the second post-operative year[ 3 , 4 , 7 , 8 ]. This risk may be higher in adolescent bariatric surgery recipients with a recent multi-center study reporting an AUD prevalence of approximately 45% eight years post-surgery[ 9 ].…”
Section: Epidemiology Of Alcohol Use After Bariatric Surgerymentioning
confidence: 99%
“…• No significant difference seen in the incidence rate of alcohol-associated diagnoses between the RYGB and SG groups 2020 Maciejewski et al [15] Retrospective White et al [17] Prospective cohort RYGB (155) SG (62)…”
Section: Rygb (8196) Sg (2012)mentioning
confidence: 99%
“…Over the past decade, SG has now replaced RYGB as the predominantly conducted bariatric procedure in the United States. While initial data on AUD after SG were mixed due to inadequate representation in studied populations, newer studies show a similarly increased risk of unhealthy alcohol use among American veterans, American teens, and adults in Norway who have undergone either RYGB or SG 14,15,17 . Head-to-head comparisons between SG and AGB or vertical banded gastroplasty are limited due to the relative obsolescence of the latter.…”
Section: Evidence Of Elevated Aud Risk After Bariatric Surgerymentioning
confidence: 99%
“…Studies have shown that alcohol exposure in young adults increased the risk of gambling, 3 smoking, 4 drug use, 5 and violence. 6 At the same time, it can also increase the risk of cardiovascular diseases, 7 digestive diseases, 8 cancers, 9 and other diseases 10 in later life. The potential risk of alcohol use and dependence peaks in young adulthood.…”
Section: Introductionmentioning
confidence: 99%